Psychometric Properties of the Mobile Phone Dependency Test (TDMB) in Argentina and its Relationship with Impulsivity - Durao, Marian (2021)
The use of cell phones has increased exponentially in most countries of the world. From a psychological perspective, different techniques have been developed to assess the level of dependence towards the use of the mobile phone, the TDMB test being one of the most used. Objective. The aim of the research was to adapt and validate the TDMB and its relations with impulsivity. Method. 339 adults residing in Argentina participated in the study, with ages between 18 and 65 years (M = 37.66; SD = 12.87), of which 74.3% were women. The evaluation included the TDMD, the UPPS-P to evaluate impulsivity and ad-hoc variables related to cell phone use. Results. Adequate psychometric properties were observed for the Argentine version of the TDMB. Likewise, relationships were observed between all dimensions of the questionnaire and impulsivity, as well as differences according to the age and gender of the participants. The scope and limits of the test are discussed, as well as its relationships with the impulsivity and daily use of the mobile phone.